2018
DOI: 10.1002/jcp.27947
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment with systemic resveratrol and resveratrol preconditioned mesenchymal stem cells, maximizes antifibrotic action in diabetic cardiomyopathy

Abstract: Wnt/β‐catenin signaling pathway plays a crucial role in diabetic cardiomyopathy (DCM), thus we aimed at investigating the effect of one therapeutic approach with resveratrol (RSV) given systemically and combined treatment of RSV with mesenchymal stem cells (MSCs) that was either RSV‐preconditioned or not on Wnt/β‐catenin signaling pathway in streptozotocin‐induced DCM, and to evaluate effects of RSV preconditioning on MSCs therapeutic potential. The rats were divided into control (C, n = 8), diabetic (DM, n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 60 publications
3
17
0
Order By: Relevance
“…Research on the protective effect of RSV on the cardiovascular system has attracted much attention, and its antioxidative and antiatherosclerotic effects have been confirmed. ShamsEldeen et al (2019) showed that systemic RSV combined with RSV-preconditioned mesenchymal stem cells to treat diabetic cardiomyopathy can maximize antifibrotic effects. In addition, studies have shown that RSV can reduce the senescence of adipose-derived mesenchymal stem cells (ADMSCs) and improve their paracrine functions, and this effect occurs by upregulating the expression of Pim-1 through the PI3K/AKT pathway ( Lei et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the protective effect of RSV on the cardiovascular system has attracted much attention, and its antioxidative and antiatherosclerotic effects have been confirmed. ShamsEldeen et al (2019) showed that systemic RSV combined with RSV-preconditioned mesenchymal stem cells to treat diabetic cardiomyopathy can maximize antifibrotic effects. In addition, studies have shown that RSV can reduce the senescence of adipose-derived mesenchymal stem cells (ADMSCs) and improve their paracrine functions, and this effect occurs by upregulating the expression of Pim-1 through the PI3K/AKT pathway ( Lei et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…RSV has been shown to prevent the progression of heart failure and improve cardiac function and survival in animal models of myocardial infarction-induced heart failure. Studies have also shown that systemic RSV combined with the transplantation of RSV-preconditioned stem cells can maximize the antifibrotic effects in the treatment of diabetic cardiomyopathy ( ShamsEldeen et al, 2019 ). However, whether RSV can rejuvenate BMSCs and improve transplantation ability in DM rats with myocardial infarction and the precise mechanism is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, BM-MSCs-derived exosomes significantly downregulated the expression of these signaling proteins with antifibrotic actions [ 102 ]. Attenuation of the pro-fibrotic FRP/Wnt/β-catenin pathway was induced by BM-MSCs preconditioned with resveratrol (RSV) resulting in enhanced cardioprotective and antifibrotic effects in diabetic cardiomyopathy [ 103 ]. Surprisingly, the most frequently prescribed antidiabetic drug, Metformin, impaired BM-MSC-mediated cardioprotection in diabetic cardiomyopathy by decreasing homing and survival of injected cells in the myocardium [ 104 ].…”
Section: Msc Therapy In Pre-clinical Models Of Cardiomyopathiesmentioning
confidence: 99%
“…Various dosages of RSV (1, 5, and 10 mg/kg) significantly decreased myocardial lesions by increasing myocardial AKT expression and decreasing caspase-3 activity during carbon monoxide-induced cardiotoxicity in rats in a dose-dependent manner [71]. RSV-pretreated MSCs showed increased proliferation and demonstrated enhanced cardiac remodeling capacity in diabetic cardiomyopathy via the attenuation of secreted frizzled-related protein-mediated fibrosis and the Wnt/β-catenin pathway [72]. The combination of RSV exposure and MSC transplantation successfully prevented doxorubicin-induced cardiomyopathy in rats via enhancing the cardiogenic differentiation and the paracrine effects of MSCs [65].…”
Section: The Effects Of Rsv On Mscs In Vivomentioning
confidence: 99%